Neuraminidase as an influenza vaccine antigen: a low hanging fruit, ready for picking to improve vaccine effectiveness. (August 2018) - Eichelberger, Maryna C; Morens, David M; Taubenberger, Jeffery K
Graphical abstract: Highlights: Neuraminidase (NA)-inhibiting antibodies are an independent correlate of vaccine efficacy. Many NA-specific antibodies bind to conserved epitopes and protect against heterologous viruses. Assays to measure NA content and immunogenicity of influenza vaccines have been developed. Abstract : Neuraminidase (NA) plays an essential role in influenza virus replication, facilitating multicycle infection predominantly by releasing virions from infected cells. NA-inhibiting antibodies provide resistance to disease and NA-specific antibodies contribute to vaccine efficacy. The primary reason NA vaccine content and immunogenicity was not routinely measured in the past, was the lack of suitable assays to quantify NA and NA-specific antibodies. These are now available and with recent appreciation of its contribution to immunity, NA content of seasonal and pandemic vaccines is being considered. An added benefit of NA as a vaccine antigen is that many NA-specific antibodies bind to domains that are well conserved within a subtype, protecting against heterologous viruses. This suggests NA may be a good choice for inclusion in universal influenza vaccines.